2002
DOI: 10.1159/000067882
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Human Leukocyte Antigen Class I Antigens in Japanese Patients with Macroscopically Diagnosed Endometriosis

Abstract: An increasing number of reports suggest that endometriosis is associated with abnormal immune function, although the etiology of the disease remains undefined. The human leukocyte antigen system (HLA) is known to play a role in the etiology of a number of diseases. This study examines the possible association between the HLA system and endometriosis. Fifty-five patients diagnosed with endometriosis by laparoscopic examination were typed for HLA class I antigens – HLA-A, -B, and -C antigens – using the standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Previous studies reported no association between HLA genotypes and endometriosis in Caucasian women with endometriosis and controls, as assessed by serological typing [46][47][48] . A serological study showed increased frequencies of the HLA-B*54 and HLA-C*07 alleles in Japanese patients with endometriosis 49 . In a recent study, PCR-restriction fragment length polymorphism analysis revealed that the HLA-DRB1*14:03 and HLA-DQB1*03:01 alleles are associated with endometriosis in Japanese women 50,51 .…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies reported no association between HLA genotypes and endometriosis in Caucasian women with endometriosis and controls, as assessed by serological typing [46][47][48] . A serological study showed increased frequencies of the HLA-B*54 and HLA-C*07 alleles in Japanese patients with endometriosis 49 . In a recent study, PCR-restriction fragment length polymorphism analysis revealed that the HLA-DRB1*14:03 and HLA-DQB1*03:01 alleles are associated with endometriosis in Japanese women 50,51 .…”
Section: Discussionmentioning
confidence: 98%
“…Several studies attempted to associate HLA class I or II to endometriosis in different populations but there are lot of aspects to be cleared. Serological and genetic studies in Japanese populations have demonstrated that susceptibility to endometriosis is associated with specific HLA class I or II alleles [9,18,19], whereas several other studies failed to relate HLA to endometriosis [7,8,[20][21][22]. Whang et al [22] analysed the distribution of HLA-DRB1 alleles in a Korean population with surgical and histological evidence of advanced endometriosis and could not find any differences with healthy female subjects, findings which are consistent with previous reports in Caucasian populations in which, utilising serological typing methods, no correlations in HLA class I or II allele distribution were found in women with endometriosis compared with controls [7,8,20].…”
Section: Discussionmentioning
confidence: 99%
“…HLA system plays a key role in the immune response and it seems that endometriosis shares many similarities with autoimmune diseases [5,6]. Possible associations between endometriosis and HLA have been reported in the literature more than two decades ago [7,8] while recently the HLA system has been implicated in the aetiology of endometriosis [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was reported that pathogenesis of endometriosis is associated with autoimmune reactions including anti‐endometrial, anti‐nuclear and anti‐phospholipid autoantibodies as well as aberrant expression of HLA class II antigens by cells of the ectopic endometrial foci (7, 8). Serological studies and accurate molecular genomic typing in a Japanese women with endometriosis showed an increased frequency of HLA‐B54 and ‐Cw7 (9) with associated HLA‐DRB1*1403 and ‐DQB1*0301 alleles (10, 11). In another molecular typing study, endometriosis in Japanese patients was associated with the allele HLA‐B*0702 in linkage disequilibrium with the HLA‐A24 , ‐Cw*0702 and ‐DRB1*0101 alleles (12).…”
Section: Statistically Significant Alleles Associated With Endometriosismentioning
confidence: 99%
“…A previous finding by Ishii et al (11) reported that the allele HLA‐DQ*0301 was also associated with endometriosis and that HLA‐DQ is a susceptibility gene. Ishii et al (9, 10) reported that HLA‐DR*1403 was associated with endometriosis. These contradictory results obtained by us and others suggest that further analyses and duplication studies are required using an increased sample size of patients and controls together with microsatellite and HLA SNP genotyping to identify and better understand the HLA susceptibility gene region for endometriosis.…”
Section: Statistically Significant Alleles Associated With Endometriosismentioning
confidence: 99%